Representation and conflict of interest among students on higher education governing boards. Issue 6 (2nd November 2017) - Lozano, Jon; Hughes, Rodney
ABSTRACT: Student participation in higher education governance is commonplace in many countries around the globe. This participation can take many forms, but one prevalent form is through the inclusion of students as members of institutional governing boards, commonly called student trustees. This practice is not without critique with governance scholars often cautioning against student board membership. They cite the potential for student members to engage in representative behaviour, which may lead them to focus primarily on student issues or cast votes which may be in the best interest of themselves or their fellow students as the primary objection to student board members. This study of student trustees in the United States examines the extent to which these individuals engage in such behaviours, examining interactions between student board members and students at their institutions for signs of whether these oft states concerns have a basis in practice.